Translational Research in a Military Organization: The Marine Corps Organizational Culture Research Project. Issue 1 (22nd February 2020) - Fosher, Kerry B.; Lane, Rebecca; Tarzi, Erika; Post, Kristin; Gauldin, Eric M.; Tashev, Blagovest; Edwards, Jennifer; McLean, Jeremy D.
Abstract: This article provides an overview of a project combining anthropological practice and research to examine various aspects of U.S. Marine Corps culture, conducted at the organization's request, in the wake of significant gender‐related misconduct involving Marines on social media. We examine the context and practice leading up to the research, address research design and execution, and describe both the broader Marine population and the characteristics of those in our sample. By examining the details of the project's context and execution, the article aims to advance anthropological discussion about the complexities of research with active duty military personnel, as well as provide insights into practice and research conducted from a standpoint within a military organization.